OCCUPATIONAL RADIATION EXPOSURE DOSE OF THE EYE IN DEPARTMENT OF CARDIAC ARRHYTHMIA PHYSICIAN. Issue 3 (12th October 2019) - Kato, Mamoru; Chida, Koichi; Ishida, Takato; Sasaki, Fumiaki; Toyoshima, Hideto; Oosaka, Hajime; Terata, Ken; Abe, Yoshihisa; Kinoshita, Toshibumi
Abstract: Interventional radiology (IR) procedures tend to be complex, which delivers high radiation exposure to patient. In the present study, we measured the radiation exposure dose [Hp(3)] in the eye using a direct eye dosemeter placed next to the physician's eye during procedures. Physicians wore a direct eye dosemeter just lateral to eyes and an additional direct eye dosemeter outside the radiation protective eyeglasses close to their eyes. Additionally, a neck glass badge was worn at the neck. Although we found a positive correlation between the left neck glass badge dose [Hp(0.07)] and the left eye lens dose [Hp(3)], the value of R 2 of the regression equation were 0.62 and 0.71 (outside and inside). We thought that the exact eye lens dose might not be estimated from the neck glass badge. In conclusion, a correct evaluation of the lens dose [Hp(3)] using the direct eye dosemeter is recommended for tachyarrhythmia physicians.